Penerapan dan Dampak Nagham Al-Qur'an: Perspektif Living Qur’an dan Teori Resepsi Wolfgang Iser - Faiza Salsabila; Nuha, Ulin (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2023)
This research uses a qualitative method with a living Qur'an theory approach and Wolfgang Iser's reception theory to examine the application of the Al-Qur'an nagham in Pasar Semerap Village. Data was collected through observation and interview methods, both secondary and primary. The main focus of this research is to explore the application of the Koran nagham in learning in the village and understand the motivation and benefits for the community. The research findings show that there is a practice of implementing Nagham science which has become an integral part of the daily life of the people of Pasar Semerap Village. The process of learning and teaching nagham Al-Qur'an does not only take place in educational institutions such as TPQ, but is also part of routine activities in mosques. The reception of Al-Qur'an nagham in this village is aesthetic and functional, which shows that reciting Al-Qur'an verses with nagham has become a tradition passed down from generation to generation. This practice not only reflects aesthetic values, but also functions as a way of life that continues to develop in society. In this way, the Koran nagham in Pasar Semerap Village has been transformed into a culture that lives and develops over time.